Academic staff utilisation of information and communication technologies (ICTs) in Nigerian tertiary institutions: a study of ten selected universities (2007)
This study examined the availability and usage of Information and Communication Technologies (ICT) by academic staff in ten selected Nigerian tertiary institutions. Data was collected using the questionnaire method. 172 copies of a questionnaire were mailed to academic staff in the 10 institutions studied out of which 136 copies were returned representing 76.2% response rate. Analysis of the questionnaire revealed the level of ICT competence and rate of ICT adoption by the academic communities vis-a-vis the facilities on ground as well as the various ways it is being used. The outcome of the study showed that ICT is gradually being accepted by tertiary institutions in Nigeria.